Influence of acetic acid dissolution time on evolution of coal phase and surface morphology. (15th February 2021) - Yang, Haotian; Yu, Yanbin; Cheng, Weimin; Rui, Jun; Xu, Qingfeng
Highlights: The reaction of acetic acid with the minerals in coal is divided into three stages. Acetic acid destroys coal crystals mainly in the vertical direction. Acetic acid helps to shorten the length of aliphatic chains. Abstract: That low porosity is the main restrictive factor of coalbed methane exploitation and the permeability of water flowing in coal for dust suppression. The existing physical infiltration technology has a good effect on creating fractures, but there are hidden dangers inducing microseismic and other aspects. The application of acidification technology to increase coal reservoirs' porosity is of great significance for coalbed methane extraction and water injection to suppress dust generation. In this paper, powdered coal samples were treated with 75% acetic acid. Different dissolution times on the composition and structure of coal samples were investigated by X-ray diffraction, Fourier infrared spectroscopy, and scanning electron microscopy. X-ray diffraction results show that the reaction of acetic acid with minerals in coal can be divided into three stages, namely the initial contact stage (1–12 h), crystal destruction stage (12–48 h), reaction slowdown stage (>48 h). The dissolution of the coal crystal structure by acetic acid is mainly to destroy the vertical layer stacking. Fourier transform infrared results show that the hydroxyl group changes significantly with the dissolution time, and acetic acid will catalyze the cleavage of aliphatic C–C bonds in coal, making the length of the fatty chain shorter. Scanning electron microscopy results show that acetic acid has an excellent corrosive effect on granular minerals on the surface of coal structures. The surface after dissolution is smooth, and dissolution pores and micro-fractures are generated.